Evaluating Project Safe Neighborhoods in Connecticut: a Youth Opportunity Initiative - Jeffries, Sara R. (Crime prevention and community safety, 2019)
Despite containing numerous wealthy geographic areas, the state of Connecticut continues to struggle with social and economic distress, along with gun-related crime. Problem analysis in urban areas revealed a critical need for services aimed at deterring violent and gun-related crime in two target populations: serious juvenile offenders, aged 14-17 years, and at-risk youth, aged 11-13 years. Using a quasi-experimental design, this study aimed to evaluate the effect of Project Safe Neighborhoods (PSN) on youth in two cities in Connecticut. Implementation resulted in 133 young people receiving a variety of services in New Haven and Bridgeport. Evaluation research assessed intervention efforts designed to (1) build on the strengths and address the challenges of each juvenile offender, (2) expand community outreach and education efforts to reinforce and reward positive attitudes and behaviors surrounding “no-gun policies,” and (3) utilize data-driven decision-making to guide program implementation and evaluate the results. Our findings suggest that youth who participated in Connecticut’s PSN Youth initiative benefited from the services provided and exhibited a decreased involvement in the juvenile justice system following enrollment.